Deceptive Self-Presentation: The Role of Social Media User Motivation and the Dark Triad Personality - Ujam Jaenudin; Elis Anisah Fitriah; Mirna Devi (Psympathic : Jurnal Ilmiah Psikologi, 2023)
Online identity frauds such as love scams, catfishing, and fake content are associated with the freedom of personalization offered by social media platforms which can lead to deceptive self-presentation behavior and impressions. Therefore, this research aimed to examine the role of motivation to use Instagram and the dark triad personality on deceptive self-presentation. It was conducted quantitatively through structural equation model (SEM) analysis based on partial least squares (PLS) using data collected from 400 early adult Instagram users between the ages of 20 and 34 years in Indonesia. The results showed that motivation to use Instagram and the dark triad personality influenced deceptive self-presentation by 30.9% on ideal self-dimension and 41.9% on false self-dimension. Moreover, motivational dimensions of gaining new friendships, following and monitoring, social connectedness and social recognition had a significant influence on deceptive self-presentation. In the dark triad personality variable, only the narcissism dimension was observed to have a significant influence on deceptive self-presentation.